The Influence of Motivation and Work Discipline on Employee Performance at The North Wara Sub-District Office, Palopo City - Mardin, Irma Anugrah; Toding, Stefani Putri; Anshar, Tika; Mattayang, Besse; Nurhuda, Nurhuda (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This research aims to analyze the influence of motivation and work discipline on employee performance at the North Wara Subdistrict Office, Palopo City. The approach used is a survey method by collecting data through questionnaires distributed to office employees. Data analysis was carried out using descriptive methods, validity and reliability tests, and multiple linear regression. The research results show that motivation and work discipline have a significant positive effect on employee performance. Increasing work discipline has been proven to increase employee productivity and orderliness in completing their tasks.